A large one-time addition of organic soil amendments increased soil macroporosity but did not affect intra-aggregate porosity of a clay soil - Rasa, Kimmo; Tähtikarhu, Mika; Miettinen, Arttu; Kähärä, Topi; Uusitalo, Risto; Mikkola, Jarmo; Hyväluoma, Jari (Soil & tillage research, 2024)
Soil structure is a dynamic property which controls a wide range of soil functions and is closely linked with soil carbon content. The carbon contents of agricultural soils are subject to several ongoing trends, including declining carbon stocks and attempts to increase the soil carbon reserves. In this study, we aimed to quantify how organic soil amendments, which have been shown to reduce long-term nutrient loads from agricultural fields, can impact soil structure. The structural impacts of a large one-time addition (8 tons carbon per hectare, three different soil amendments) of pulp and paper mill side stream sludges to a boreal clay soil were explored quantitatively in aggregate (X-ray microtomography, sample size 1–2 mm), core (water retention measurements, sample size 195 cm3) and column (macropores ≥80 µm, sample size ∼ 20 dm3) scales. Our results showed no micrometer-scale structural changes within soil aggregates despite the large number (25 aggregate per treatment) of imaged samples. However, the organic soil amendments had a statistically significant impact on the macroporosity. The macroporosity was on average 20–27 % higher compared to the control samples and visible even five years after the application of the amendments. Such change in soil structure improves soil aeration and fast infiltration of water during wet periods and extreme rain events and may thereby also reduce erosion risk by decreasing surface runoff. The increased microporosity was visible only in the column scale. No statistically significant differences were observed in the fraction of large pores in core scale water retention measurements. Probing the soil structural changes in macropore regime by X-ray tomography or developing sub-micron scale analysis methods are recommended approaches to improve our understanding of clay soil’s structural changes induced by organic soil amendments. •The effect of a large single dose of organic matter on soil structure was studied.•Soil structure was investigated from aggregate to column scale.•100 aggregates imaged with X-ray tomography.•Differences in intra-aggregate porosity were not found.•Only macropores (≥80 µm) were affected by the organic soil amendments.